Optimization of Nutrition in Soilless Systems: A Review - Gorbe, Elisa; Calatayud, Ángeles (2017)
High yield and product quality of crops grown in soilless systems are only possible if nutrition is optimized. This implies the accurate management of all factors involved in crop nutrition: nutrient solution composition, water supply, nutrient solution temperature, dissolved oxygen concentration, electrical conductivity and pH of the nutrient solution. If any of these factors is under non-optimal conditions, plants may suffer from stress leading to a decline of yields and product qualities. In order to specify the range of optimal conditions of a particular crop, a precise diagnosis of plant stress caused by an incorrect management of any of above mentioned factors is needed. This review analyses, for every factor, the aspects that need to be considered while determining the optimum ranges and the physiological methods that can be used to diagnose plant stress at non-optimal conditions. The most extensively used methods of plant stress assessment include measurements of: photosynthetic activity (leaf gas exchange, chlorophyll fluorescence, pigment content and related enzyme activities), oxidative stress and antioxidant capacity, content and partitioning of several compounds in the plant (carbohydrates, hormones, amino acids and nutrient elements), activity of specific enzymes, plant water relationships and expression of specific genes.